Effect of different light sources and reinforcement fibers on the hardness of dual resin cements activated through an indirect composite resin - Kummer, Gabriela dos Santos; Takahashi, Marcos Kenzo; Archegas, Luci Regina Panka; Rached, Rodrigo Nunes; Souza, Evelise Machado de (Archives of Oral Research, 2013)
Objective: The aim of this study was to determine the hardness of dual-cured resin cements irradiated with quartz-tungsten-halogen (QTH) or light-emitting diode (LED) curing units through a dental composite reinforced with different types of fibers. Material and methods: Discs made with a laboratory composite were used to simulate indirect restorations reinforced with unidirectional and bidirectional glass fibers and triaxial woven and biaxial braid ultra-high-molecular-weight polyethylene fiber ribbons. Specimens were made in a teflon mold with dual-cured resin cements (Bifix QM, RelyX ARC, RelyX Unicem, and Variolink II) and cured through a non-reinforced (control) or fiber-reinforced (Ribbond, Vectris, Fibrex-Lab, and Connect) composite discs with QTH or LED curing unit for 40 sec. The specimens were stored under 100% humidity at 37°C for 24 h. The microhardness Knoop test was carried out under a 50 g load for 15 sec, with five indentations per specimen. Data were analyzed with three-way analysis of variance (ANOVA) and Games-Howell test (p≤0.05). Results: Bifix QM showed significantly higher hardness values, despite the fiber type used in the composite reinforcement (p<0.05). Ribbond reinforcement resulted in significantly higher hardness of the resin cements, with the exception of RelyX Unicem. Resin cements activated by a LED curing unit showed statistically higher values of hardness. Conclusion: The triaxial woven polyethylene fiber reinforcement allowed better curing of most of the dual-cured resin cements. The use of a LED curing unit with higher irradiance increased the hardness of the resin cements evaluated in this study.